A rapid evaluation method based on natural frequency for post-earthquake traffic capacity of small and medium span bridges. (1st April 2023) - Tan, Guojin; Li, He; Wang, Wensheng; Kong, Qingwen; Jiang, Lin; Zhang, Sufeng; Wei, Xueliang
Graphical abstract: Highlights: Post-earthquake bearing capacity of pier is calculated by natural frequency. Fitting accuracy optimization by increasing axial compression ratio variable. Quick estimate of the weight of a vehicle that can pass a post-earthquake bridge. Pier model and the equation based on residual displacement are validated by tests. Abstract: To improve the efficiency of evaluating the traffic capacity of bridges after the earthquake, a rapid method based on natural frequency for evaluating post-earthquake traffic capacity of small and medium-span bridges is proposed. Firstly, OpenSees software is selected to establish the seismic numerical analysis model of the pier, and the pressure of the main girder on the pier is equivalent to concentrated mass to extract the dynamic characteristics of the pier. The horizontal thrust on the pier top is adopted to simulate seismic action by the pseudo-static method, and the horizontal thrust is controlled by the maximum horizontal displacement. The value range of pier parameters is determined according to the definition of the regular bridge and relevant design data, then the design parameters and maximum horizontal displacement of each pier are sampled by the Latin hypercube sampling method to obtain various combined working conditions. Subsequently, the natural frequency, residual displacement and bearing capacity of the pier under different working conditions are obtained through numerical simulation. The relationship between natural frequency and residual bearing capacity of the pier after the earthquake is established in light of the simulation results of pier models. Then, the vehicle load is arranged on the basis of the most unfavorable loading principle, and the bearable maximum vehicle weight of the bridge is estimated from the bearing capacity of each pier, so that the traffic capacity of the bridge after the earthquake can be quickly evaluated by the change of natural frequency of piers. Finally, the reliability of the pier numerical model and residual displacement calculation method are verified by the test results of piers. The application process of the evaluation method proposed in this paper is illustrated by two typical examples of a simply supported beam bridge and a continuous beam bridge, which proves the feasibility of this method.